2012
DOI: 10.1088/1367-2630/14/3/033020
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent trapping and delivery of submicro-spheres using a submicrofibre

Abstract: We report size-dependent trapping and delivery of polystyrene submicro-spheres using a 600 nm diameter fibre. Theoretical results show that both gradient and scattering forces exerted on polystyrene submicro-spheres by the evanescent wave field around the submicrofibre increase with an increase in the sphere diameter, and the delivery velocity of the bigger spheres is also higher than that of smaller spheres. To support the theoretical predictions, experiments were performed using polystyrene spheres with diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
(34 reference statements)
3
21
0
Order By: Relevance
“…From the particle trajectory analysis result in Figure 4, we can find that the trapped microparticle moved at a somewhat uniform velocity and the averaged propulsion velocity was calculated to be approximately 20.23 μm·s −1 from a linear fit to the trajectory, with a similar scale like that reported in Reference [9]. It has been reported that large-size spheres can be trapped more easily and delivered much faster than small ones [9,11]. Nevertheless, the observed propulsion speed of the trapped microparticles with diameters of 5 μm here is larger than that in the previous work using a slightly tapered telecom single-mode optical fiber and microparticles with diameters of 10 μm [13].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…From the particle trajectory analysis result in Figure 4, we can find that the trapped microparticle moved at a somewhat uniform velocity and the averaged propulsion velocity was calculated to be approximately 20.23 μm·s −1 from a linear fit to the trajectory, with a similar scale like that reported in Reference [9]. It has been reported that large-size spheres can be trapped more easily and delivered much faster than small ones [9,11]. Nevertheless, the observed propulsion speed of the trapped microparticles with diameters of 5 μm here is larger than that in the previous work using a slightly tapered telecom single-mode optical fiber and microparticles with diameters of 10 μm [13].…”
Section: Resultssupporting
confidence: 67%
“…If the laser light source is replaced by a new one with an infrared wavelength [13], under which the optical absorption and heating effect of the silica glass fiber can be reduced, the observed propulsion speed will be at the same scale as the other reports [7,8,10,12,13]. The high propulsion speed of the trapped particle is also reported in Reference [11], where the wavelength of the used laser source is also 532 nm. On the other hand, the slight swinging of the temporal trace of the particle position along the tapered fiber results from the slightly nonuniform propulsion velocity, which is attributed to the residual polymer coating obstacles on the stripped tapered fiber surface.…”
Section: Resultsmentioning
confidence: 68%
“…22 These velocities were more than an order of magnitude higher than that observed in previous studies. [6][7][8][9][10][11][12] Theoretically, we showed that the peak force can approach the level that an absorbing particle would experience based on the total momentum transfer from light to microparticle. 22,25 These experiments were carried out with an assembly of microspheres interacting with the tapered fiber.…”
Section: Introductionmentioning
confidence: 89%
“…4 However, the resonant force peaks have been relatively weekly pronounced in these experiments since a focused laser beam illumination did not produce strong coupling to whispering gallery modes (WGMs) in spheres. Since that time the ways of exerting light forces using evanescent fields have been developed using prism couplers 5 , surface waveguide [6][7][8][9] and tapered fiber [10][11][12] . However, the resonant peaks of the light forces in these experiments have not been observed or they have been relatively weakly pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…At DP ¼ 0 and v ¼ 0 mm s À1 , the particles were halted on the fiber. The scattering force (F s ) can be calculated by using Stokes law F ¼ 6prhn, [20][21][22] where r ¼ 356.5 nm is the radius of the particle and h ¼ 8.9 Â 10 À4 Pa s is the dynamic viscosity of water at room temperature. The results of F s are also shown in Fig.…”
mentioning
confidence: 99%